Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas VIII.B SMP Negeri 33 Makassar - Rosmawati, Hj. (Universitas Negeri Makassar, 2018)
This study aims to improve the learning outcomes of IPS through the implementation of cooperative learning model of snowball throwing type in students of class VIII.B SMP Negeri 33 Makassar. The type of research is action research. The focus of research is the type of cooperative learning model of snowball throwing and IPS learning outcomes. Data were collected using observation, test, and documentation, while the research data was analyzed descriptively. The results of the study that IPS learning outcomes can be increased through the application of cooperative learning model of snowball throwing type. Cycle I, IPS learning outcomes including good category but not yet reached the defined learning completeness criteria, then cycle II is in very good category and has reached defined learning completeness criteria. The increase of learning result of IPS through the implementation of cooperative learning model of snowball throwing type is supported by the increase of students' learning activity, such as: student activeness and group leader listening teacher explanation related to material / theme, making questions, answer written questions in ball-shaped paper, IPS lessons on the theme of location excellence and the life of Indonesian society.